Effect of Bitter Leaf Extract (Andrographis paniculata) against Edwardsiella tarda Bacteria In vitro - Giri Pratama; Arief Prajitno; Titik Dwi Sulistiyati; Desy Amalia Hidayati; Tania Nilakhandi (Journal of Aquaculture and Fish Health, 2023)
This study aimed to determine the antibacterial activity of bitter leaf extract (A. paniculata) against the growth of E. tarda bacteria. This test was carried out using Kirby Bauer method (disc test) using five different concentrations, namely 50 mg/L, 100 mg/L, 150 mg/L, 200 mg/L, and 250 mg/L in TSA (Tryptone Soya Agar) and incubated for 2x24 hours using a temperature of 30 oC. The positive control used was chloramphenicol (5 mg/L), while the negative control used PBS. Bitter leaf extract contains active compounds that have bacteriostatic antibacterial properties. After incubation for 24 hours the concentration of 250 mg/L showed the highest inhibition zone with a diameter of 7.82 mm and decreased at 48 hours to 7.46 mm. After being incubated for 24 hours, the concentration of 250 mg/L obtained an effectiveness value of 57.08% which is the best effectiveness, and there was a decrease in the 48th hour to 54.45%.